Securitization VS. Desecuritization: Sino-American Strategic Competition in Southeast Asia - Sae-lo, Chuthamat (รัฐศาสตร์นิเทศ, 2022)
Southeast Asia has become the new terrain of great powers competition. The influence of the United States, a leader of the free world, is challenged by the rising communist China. On the one hand, China’s increasingly assertive foreign policy in territorial disputes with its neighbors has destabilized peace and security in the region. On the other hand, the intentions behind Chinese soft power deployment through Belt and Road Initiatives (BRI) are suspected as Beijing aims to dominate its backyard countries in Southeast Asia. This paper, therefore, presents the strategic assessment of Sino-American competition in Southeast Asia. The first section explores the deployment of Washington’s strategy (securitization of China) and Beijing’s strategy (desecuritization) to catch Southeast Asian attention. With this background, the second section discusses the challenge posed by desecuritization strategy of China through the BRI. The pragmatic-oriented foreign policy, debt-trap diplomacy, aid assistance led by Chinese state-owned enterprises, and the inconsistency of American foreign policy have intensified the success of Chinese grand strategy which is characterized as deceptive agendas. Assuming from the current situation, there are three possible scenarios to occur. The third section predicts the worst-case scenario of Chinese neo-colonialism in Southeast Asia. The ‘self-reliant’ Southeast Asian states are the future best-case scenario described in the fourth section. In the fifth section, the intractable great powers conflict and the hum and haw foreign policy of ASEAN nations reflect the business as usual. To avoid the worst-case and move beyond the business as usual, the two possible solutions are demonstrated in the sixth section. In this section, the analysis focuses on each Southeast Asian state’s capacity development and the collective efforts in strengthening the robust regional organization, respectively. Finally, the present paper proposes five strategic recommendations to ASEAN in order to be able to deal with the external challenges and attain the ultimate benefits for its member states.